(untitled) (Agricultural Engineering, 2016)
The paper examines the selected physical properties of seeds of 8 plants used in agri-food processing industry. These are: winter rapeseed (Brassica napus L.) Adriana cultivar, sesame (Sesamumindicum L.), common flax (Linum usitatissimum L.) Luna cultivar, husked sunflower (Helianthus L.) (country of origin – Bulgaria), hemp (Cannabis sativa L.) Benikocultivar, blue poppy (Papaver somniferum L.) Major cultivar, garden cress (Lepidium sativum L.), black caraway (Nigella Sativa L.). In the research material we determined the following: mass of thousand seeds (MTS), piling angle and angle of repose, tap and bulk density and compressive resistance of single seeds. Some seeds from the selected plant species differed with shape and size. Thus, the results determining the physical properties were varied.